2013
DOI: 10.1371/journal.pone.0082082
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blocker Enhances Beneficial Effects of an Angiotensin II AT1 Receptor Blocker against Cerebrovascular-Renal Injury in type 2 Diabetic Mice

Abstract: Recent clinical trials have demonstrated that combination therapy with renin-angiotensin system inhibitors plus calcium channel blockers (CCBs) elicits beneficial effects on cardiovascular and renal events in hypertensive patients with high cardiovascular risks. In the present study, we hypothesized that CCB enhances the protective effects of an angiotensin II type 1 receptor blocker (ARB) against diabetic cerebrovascular-renal injury. Saline-drinking type 2 diabetic KK-Ay mice developed hypertension and exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Additionally, a recent study showed that ARB plus CCB has beneficial effects against cerebrovascular-renal injury in type 2 diabetic mice [18]. Consistent with previous studies [19], [30], the present study showed that in DSS rats, 4 weeks of treatment with HS diet caused hypertension, proteinuria, glomerular and tubulointerstitial damage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, a recent study showed that ARB plus CCB has beneficial effects against cerebrovascular-renal injury in type 2 diabetic mice [18]. Consistent with previous studies [19], [30], the present study showed that in DSS rats, 4 weeks of treatment with HS diet caused hypertension, proteinuria, glomerular and tubulointerstitial damage.…”
Section: Discussionsupporting
confidence: 92%
“…Gene expression in renal cortical tissue was analyzed by RT-PCR using a LightCycler FastStart DNA Master SYBR Green I kit and an ABI Prism 7000 Sequence Detection System (Applied Biosystems, Foster City, USA) as described previously [18] , [23] . The oligonucleotide primer sequences for rat β-actin, TGF-β 1 , α-SMA, type 1 collagen, MCP-1, PAI-1, gp91phox, Nox-1, E-cadherin, and fibroblast-specific protein 1 (FSP-1) are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High blood pressure is a risk factor for diabetic nephropathy [27,28]. In previous reports, olmesartan inhibited albuminuria in diabetic animals, but this effect was not tightly correlated with blood pressure control [16,17,20,29]. Of course, we cannot exclude that the reduced blood pressure by olmesartan treatment contributed to the decreased albuminuria in db/db mice, however the focus of our study was to investigate the effect of olmesartan on angiotensin II/SIRT1 pathway triggered podocyte apoptosis.…”
Section: Discussionmentioning
confidence: 86%
“…The combination therapy of ARBs plus CCBs was reported to be more effective than monotherapy (Ogawa et al, ). In fact, olmesartan plus azelnidipine enhanced cerebrovascular and renal protective effects by suppressing NADPH oxidase‐dependent oxidative stress (Rafiq et al, ) and showed antiatherogenic effects by suppressing oxidative stress and activating endothelial nitric oxide synthase (Noda et al, ). In a clinical study for type 2 diabetic hypertensive patients, the combination of olmesartan plus azelnidipine was more beneficial against BP morning surge, showed a greater decrease in heart rate, and improved glucose tolerance and microalbuminuria more than candesartan plus amlodipine therapy (Daikuhara et al, ).…”
Section: Discussionmentioning
confidence: 99%